Spatial mapping and determinants of intimate partner violence among married women in Sierra Leone: A cross-sectional study - Augustus Osborne; Umaru Sesay; Camilla Bangura; Lovel Fornah (PLoS ONE, 2025)
Background Intimate partner violence is a pervasive public health and human rights issue, disproportionately affecting women worldwide. In Sierra Leone, where gender inequalities and socio-cultural norms remain entrenched, intimate partner violence is a significant concern, with severe consequences for women’s physical, emotional, and social well-being. Understanding the spatial distribution and determinants of intimate partner violence is crucial for designing targeted interventions to address this issue. Using data from the 2019 Sierra Leone demographic and health survey, this study explored the geographic patterns of intimate partner violence and identified key socio-demographic and behavioural factors associated with its prevalence among married women. Methods The study employed data from the 2019 Sierra Leone demographic and health survey. The study comprised of 3,611 married women between the ages of 15 and 24. Spatial autocorrelation and Moran’s I statistic were employed to analyse the spatial distribution of intimate partner violence. The study utilised mixed-effect multilevel binary logistic regression using a four-model framework to determine the factors related to intimate partner violence. The findings were presented as adjusted odds ratios (aOR) and a 95% confidence interval (CI). Results The study revealed an overall intimate partner violence prevalence of 56%, with physical violence accounting for 38.2%, sexual violence for 6.2%, and emotional violence for 45.9% among married women in Sierra Leone. Hotspot districts for intimate partner violence were identified in the Western area (urban and rural areas) and the Northwestern province (Kambia and Karene). At the same time, Bo, Kenema, and Bombali, the provincial headquarters of the Northern, Eastern, and Southern provinces, were found as cold spot districts for intimate partner violence. Factors associated with intimate partner violence included married women aged 25–29, those with one-two partner controlling behaviour, and those who provided one-two justifications for wife beating. Furthermore, married women exposed to interparental violence and those who resided in the Northwestern, Northern, and Western area had a higher likelihood of experiencing intimate partner violence. Conclusion The high prevalence of intimate partner violence, particularly in hotspot districts like the Western and Northwestern province, underscore the need for province-specific interventions to protect women and reduce violence. Efforts should focus on challenging harmful cultural norms that justify wife-beating and controlling behaviours while also addressing the intergenerational cycle of violence by supporting women exposed to interparental violence. Policies must prioritise targeted education, community engagement, and enforcement of laws against intimate partner violence. Integrating intimate partner violence prevention into broader health, social, and legal systems is essential to ensure a coordinated and sustainable response to this pervasive issue.